Hypotension in Newborn Infants and Its Treatment - Fahrettin Uysal; Özlem Mehtap Bostan; Evren Semizel; Filiz Akaltun; Gülcan Üner; Ergün Çil (Güncel Pediatri)
Systemic hypotension is a common complication of sick premature infants and may be associated with major adverse outcomes, including intraventricular hemorrhage, neuro-developmental morbidity, and mortality. There is no consensus among neonatologists regarding either the definition of hypotension or the lower threshold level of systemic arterial blood pressure in which neurological injury is inevitable. For this reason, there is a considerable variation in the reported prevalence of hypotension among different neonatal units. However, it is widely accepted by many of clinicians that early and aggressive treatment of hypotension in the neonates leads to improved neurologic outcome and survival. The goal of treatment of hypotension is to maintain adequate organ blood flow, particularly, cerebral blood flow. Because of difficulties in evaluating organ perfusion and adequacy of cerebral oxygen delivery, treatment decisions are based on statistically defined gestational and postnatal age-dependent normative blood-pressure values combined with clinical intuition. Current treatment of hypotension in the premature infant includes the use of volume expansions, inotropes, vasopressor agents and corticosteroids. It has been reported that dopamine, as a commonly used inotropic agents in the neonatal period, is more effective than dobutamine in the raising of blood pressure. Some hypotensive premature infants have low cortisol levels because of adrenocortical insufficiency, and corticosteroids are generally reserved for treatment of refractory hypotension of these infants; however, it is not recommended for prophylaxis or routine clinical use because of its potential serious side effects. This article aims to review some of the controversies about diagnosis and management of systemic hypotension in the newborn infants. (Journal of Current Pediatrics 2013;11:68-76)